Edge bearing tests to assess the influence of radial gradation on the transverse behavior of bamboo. (30th January 2017) - Moran, Richard; Webb, Kelly; Harries, Kent; García, José Jaime
Highlights: Edge bearing tests, DIC, and finite element simulations to characterize bamboo circumferential behavior. Three circumferential modulus distributions were proposed for three bamboo species. Circumferential failure stresses and strains were determined. Typical and atypical failures are described in standard edge bearing test. Abstract: Bamboo is a sustainable material with high potential for structural applications. The aim of this study was to use edge bearing tests, digital image correlation analysis, and finite element simulations to research about the distribution of the circumferential elastic modulus through the wall and the associated failure strain and stress. Studied bamboo species were Phyllostachys edulis (Moso), Bambusa stenostachya (Tre Gai) and Guadua angustifolia (Guadua). Using the edge bearing tests, the effective circumferential moduli under compression were similar to those obtained under tension. Mean effective moduli were 1358.5 MPa, 662 MPa, and 862 MPa for bamboo Moso, Tre Gai, and Guadua, respectively. Linear, exponential and parabolic functions that were proposed to represent the circumferential modulus provided a relatively good fitting of the experimental results. Due to the radial gradation, the circumferential moduli at the outer position were 2.3, 1.9, and 2.6 higher than those at the inner location for Moso, Tre Gai, and Guadua, respectively. Mean circumferential failure strains and stresses in the inner culm surface were: 6693 με and 7.6 MPa; 13137 με and 12.1 MPa; and 5948 με and 3.7 MPa for Moso, Tre Gai and Guadua respectively.